Forward price, renewables and the electricity price: The case of Italy - Valeria Di Cosmo (The Economic and Social Research Institute (ESRI), 2015)
This paper investigates the determinants of the Italian electricity price (PUN) in order to determine the major challenges this market is currently facing. The results suggest that the policy maker should be aware that the importance of market expectations is increasing (captured in the model by the forward electricity price) and this may be used to understand and forecast the dynamics of spot prices. Second, the positive link between fuel prices and the Italian electricity price may lead to a greater exposure of the Italian electricity price to fluctuations in the international fuel markets. However the results show that the risks associated with higher fuel prices are partially mitigated by the presence of wind generation installed in the system.
Keywords: 330; electricity price; forward market; gas price